2010
DOI: 10.1055/s-0029-1218765
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient, One-Pot, Regioselective Synthesis of 1,4-Diaryl-1H-1,2,3-triazoles Using Click Chemistry

Abstract: An efficient, one-pot, regioselective synthesis of 1,4-diaryl-1H-1,2,3-triazoles is described via the copper(I)-catalyzed reaction of diaryliodonium salts, sodium azide and terminal alkynes. The generality of this protocol is demonstrated by the synthesis of a series of 1,4-diaryl-1H-1,2,3-triazoles in good to high yields. The catalyst and reaction solvent are reused without any appreciable reduction in product yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 3 publications
2
26
0
Order By: Relevance
“…The ligand, 2-(1-(4-methyl-phenyl)-1H-1,2,3-triazol-1-yl)pyridine (L 2 ), was synthesized and characterized as described previously [5,7]. A mixture of 1-azido-4-methylbenzene (0.75 g; 5.63 mmol) and 2-ethynylpyridine (0.69 g; 6.75 mmol, 1.2 eq) was dissolved in a 1:1 mixture of water/tertbutyl alcohol (100 ml).…”
Section: Synthesis Of 2-(1-(4-methyl-phenyl)-1h-123-triazol-1-yl)pymentioning
confidence: 99%
“…The ligand, 2-(1-(4-methyl-phenyl)-1H-1,2,3-triazol-1-yl)pyridine (L 2 ), was synthesized and characterized as described previously [5,7]. A mixture of 1-azido-4-methylbenzene (0.75 g; 5.63 mmol) and 2-ethynylpyridine (0.69 g; 6.75 mmol, 1.2 eq) was dissolved in a 1:1 mixture of water/tertbutyl alcohol (100 ml).…”
Section: Synthesis Of 2-(1-(4-methyl-phenyl)-1h-123-triazol-1-yl)pymentioning
confidence: 99%
“…[76,77] A recent study revealed the commercially available copper catalyst CuBr(PPh 3 ) 3 to be active in comparatively low catalyst loading (0.5 mol%) at room tem-perature in water without using any additives. [79] [78] Furthermore, diaryliodononium salts as substrates can be readily transformed with sodium azide and alkynes in a three-component reaction into 1,4-disubstituted 1,2,3-triazoles.…”
Section: Azide Formation Via Nucleophilic Aromatic Substitutionmentioning
confidence: 99%
“…Even though this reaction was carried out without β‐CD, surprisingly the conversion from 1a to the adduct 3aa proceeded to completion slowly. This interesting result was probably due to the polyether–water system . Polyethylene glycol (PEG) can be considered a cosolvent in water, and the consequent increase in solubility of the organic molecules has led to the application of PEG as a solvent and a PTC in organic synthesis .…”
Section: β‐Cd Effects On Cuaac Of Gap Polymer (1a) With Phenylacetylementioning
confidence: 99%
“…This interesting result was probably due to the polyether-water system. 15 Polyethylene glycol (PEG) can be considered a cosolvent in water, and the consequent increase in solubility of the organic molecules has led to the application of PEG as a solvent and a PTC in organic synthesis. 16 Like this PEG-water system, polyether linkage in GAP polymers might enable this reaction to proceed.…”
mentioning
confidence: 99%